Unshakable hope : building our lives on the promises of God - Lucado, Max (Nashville, Tennessee : Thomas Nelson, 2018)
Max Lucado offers encouraging, practical guidance for overcoming difficult circumstances and gaining inner peace, building resolve, and walking into a better future.
Includes bibliographical notes (pages 213-216).
Keywords: Christian life; God (Christianity) -- Promises; Trust in God; Hope -- Religious aspects -- Christianity